Australian mental health consumers' and carers' experiences of community pharmacy service. (11th March 2014) - Knox, Kathy; Kelly, Fiona; Mey, Amary; Hattingh, Laetitia; Fowler, Jane L.; Wheeler, Amanda J.
Abstract: Background: Many Australians with anxiety or depression experience issues accessing pharmacological treatment even though community pharmacies are remunerated to supply subsidized medicines and provide medicine management services. Objective: To obtain insight into the quality of community pharmacy services from the perspectives of mental health consumers and carers. Methods: A computer‐assisted telephone interview was used to gauge perceptions of pharmacy service using frameworks of service quality and patient‐centred care. A convenience sample of 210 consumers and carers from three Australian states completed an interview comprising rating scales, multiple choice checklists and open‐ended questions to explore their experience of pharmacy services. Results: Participants were consumers experiencing on‐going mental health condition(s) ( n  =   172), carers for someone who experienced a mental health condition ( n =  15) or both ( n =  23). For 60% of participants, medicines were dispensed within ten minutes of arriving at the pharmacy, and 36% received verbal advice. The majority of participants were not asked by pharmacy staff whether they experienced side‐effects, and 60% reported rarely or never receiving written medicine information. However, the majority of participants reported that their expectations were met despite the absence of such services. Qualitative data showed that participants valued high‐quality services that reflected patient‐centred care, and they were inclined to engage with these services particularly if they perceived them as surpassing basic expectations. Discussion and conclusions: Participants clearly valued high‐quality pharmacy service yet did not routinely expect it. When service exceeded expectations, community pharmacies were viewed as safe health‐care spaces to seek advice on mental health and well‐being. This study has positive implications for the role of pharmacists.